2006
DOI: 10.1080/00220380600576490
|View full text |Cite
|
Sign up to set email alerts
|

Higher education and economic growth in Africa

Abstract: This paper uses panel data over the 1960-2000 period, a modified neoclassical growth equation, and a dynamic panel estimator to investigate the effect of higher education human capital on economic growth in African countries. We find that all levels of education human capital, including higher education human capital, have positive and statistically significant effect on the growth rate of per capita income in African counties. Our result differs from those of earlier research that find no significant relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
113
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 211 publications
(128 citation statements)
references
References 32 publications
11
113
0
4
Order By: Relevance
“…Barro (2001) shows via 3SLS that scores and schooling years have a strong positive relation with per capita GDP growth, whereas Appiah and McMahon (2002) show that the per capita growth effects of enrollment rates are not significant. Furthermore, Gyimah-Brempong et al (2006) using the Arellano-Bond dynamic panel data estimator, find that schooling years have a positive effect on per capita growth. Via Pooled Least Squares (PLS), Keller (2006) shows that enrollment rates and primary education expenditure contribute highly significantly to GDP per capita growth.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Barro (2001) shows via 3SLS that scores and schooling years have a strong positive relation with per capita GDP growth, whereas Appiah and McMahon (2002) show that the per capita growth effects of enrollment rates are not significant. Furthermore, Gyimah-Brempong et al (2006) using the Arellano-Bond dynamic panel data estimator, find that schooling years have a positive effect on per capita growth. Via Pooled Least Squares (PLS), Keller (2006) shows that enrollment rates and primary education expenditure contribute highly significantly to GDP per capita growth.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…It is also seen that political freedom has a weak influence on economic growth. Gyimah-Brempong et al (2006) tested the expanded neoclassical growth model with the panel GMM method to investigate the effect of higher education on economic growth in African countries during the period of 1960-2000. As a result of the research, they found that primary, secondary and tertiary education which they use as education level positively affects economic growth.…”
Section: Empirical Literaturementioning
confidence: 99%
“…[6] The very same concept and significance of employability, which can be found in all the main documents of the Bologna process, has changed dramatically (Puhakka et al, 2010). [7] Moreover, although there is extensive economic literature pointing towards a positive link between investing in human capital -and in higher education -and economic growth (Murphy et al, 1991;Lucas, 1988;Stephan, 1997;Chatterji, 1998;Jaoul, 2002;Kwabena et al, 2006), empirical research exploring the former and graduates' employment is relatively more rare (Erdem & Tugcu, 2012). In fact, the majority of studies often analyse the wage premiums of tertiary education, providing overwhelming evidence about the positive returns of education on wage levels.…”
Section: Introductionmentioning
confidence: 99%